Ru+3, Rh+3, Pd+2,Pt+4 and Au+3 Metal ions Complexes with Azo Derived from 4-Aminomethyl-cyclohexane carboxylic acid Synthesis, Characterization, Thermal Study and Antioxidant Activity - Hamza, Isam Shaker; Al-Daffaay, Rasha Khider Hussain; Faris, Saja S.; Al-Hamdani, Abbas Ali Salih (Iraqi Journal of Science, 2025)
The researchers aimed to develop a novel azo ligand as a continuation of their prior investigations. They synthesized the ligand, identified as N-(3-acetyl-2-hydroxy-5-methyl-phenyl)N-(4-carboxy-cyclohexylmethyl)-diazonium salt, and proceeded to synthesize a series of chelate complexes with Ru+3, Rh+3, Pd+2, Pt+4, and Au+3 ions. Characterization of these compounds includes advanced techniques including elemental analysis, UV-Vis spectroscopy, FT-IR spectroscopy, LC-Mass spectrometry, NMR spectroscopy plus thermal analysis, conductivity measurements, magnetic quantification using TGA and DSC are used to further clarify the and synthesized complexes have been developed.Analysis revealed that the complexes formed with Ru+3, Rh+3, Pt+4, and Au+3 ions exhibited a 1:1 metal-ligand ratio and displayed octahedral geometry, with the exception of Pd+2 and Au complexes, which displayed square planar geometry. The ligand itself was found to be tridentate (NOO) in nature. The thermal decomposition of some compounds using the TGA and DSC was studied and mass spectroscopy. The dye and the complexes were determined their ability to inhibit free radicals by measuring their ability as antioxidants using DPPH as a free radical and ascorbic acid as a standard substance, and determining the value of IC50, as it was found that the ligand had a high ability to inhibit free radicals, and the ability to inhibit the complexes varied according to the value of IC50.The results are as follows (Ascorbic acid ˃ Au-complex ˃ Pt-complex ˃ Pd-complex ˃ LH ˃Ru-complex